Frequency of post‐tonsillectomy hemorrhage relative to time of day. (30th September 2019) - Kim, Sun Joo; Walsh, Jonathan; Tunkel, David E.; Boss, Emily F.; Ryan, Marisa; Lee, Andrew H.
Abstract : Objectives: Postoperative hemorrhage is a serious complication of tonsillectomy, with secondary bleeding rates affecting up to 0.8% to 3% of patients. Although these bleeds are anecdotally perceived as occurring more frequently at night, the occurrence of hemorrhage relative to the time of day has not been investigated. We measured the frequency of post‐tonsillectomy hemorrhage onset relative to the time of day. Methods: We reviewed electronic medical records of all patients who experienced postprocedural hemorrhage (International Classification of Disease, Ninth Edition [ICD‐9] 998.11, ICD‐10 J95.830 at two hospitals within a tertiary academic health system in a 10‐year period). Patient demographics, time of bleed onset, emergency room [ED] arrival time, and management (operating room vs. observation) were abstracted. Patients without a recorded bleeding time were excluded. Time of bleed onset was categorized as morning (6:01 am–12 pm), afternoon (12:01 pm–6 pm), evening (6:01 pm–12 am), or overnight (12:01 am–6 am). Chi‐square goodness of fit test was used to assess the distribution of hemorrhage timing ( P  ≤ 0.05). Results: A total of 7, 396 patients underwent tonsillectomy May 2008 through May 2018, among whom 121 (2%) post‐tonsillectomy hemorrhage patients were identified. Among the 104 patients with ED arrival times, 29 (28%) arrived in the morning; 15 (14%) arrived in the afternoon; 40 (38%) arrived in the evening; and 20 (19%) arrived overnight ( P  = 0.003). Sixty patients (mean age 17.1 years, standard deviation 16.6) had a recorded timing of bleed onset. Bleed onset occurred most commonly overnight (24, 40%), followed by evening (21, 35%), afternoon (11, 18%), and morning (4, 7%) ( P  = 0.0007). Conclusion: In this cohort, post‐tonsillectomy hemorrhage occurred most frequently between midnight and 6 am. Our findings confirm anecdotal experience and provide data in setting caregiver expectations. Level of Evidence: 4 Laryngoscope, 130:1823–1827, 2020